2009
DOI: 10.1185/03007990903350011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pioglitazone/metformin fixed-dose combination therapy compared with pioglitazone and metformin monotherapy in treating patients with T2DM

Abstract: Overall, treatment with pioglitazone/metformin FDC demonstrated greater efficacy than its individual components. The FDC therapy was well tolerated, with reduced or similar adverse event rates compared with each individual monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 18 publications
1
45
0
2
Order By: Relevance
“…Proportions taking sulfonylurea and metformin were both higher in subjects taking pioglitazone. The combination of metformin with pioglitazone offered an effective, durable and additive control of blood glucose and lowered the risk of mortality and cardiovascular events [8,38,39]. In contrast, sulfonylurea is known to be unfavorable in terms of cardiovascular risk compared with metformin [40].…”
Section: Discussionmentioning
confidence: 97%
“…Proportions taking sulfonylurea and metformin were both higher in subjects taking pioglitazone. The combination of metformin with pioglitazone offered an effective, durable and additive control of blood glucose and lowered the risk of mortality and cardiovascular events [8,38,39]. In contrast, sulfonylurea is known to be unfavorable in terms of cardiovascular risk compared with metformin [40].…”
Section: Discussionmentioning
confidence: 97%
“…9 In a double-blind parallel study, this metformin/pioglitazone fixed combination was shown to be more effective in achieving target HbA1c levels than the individual monotherapies. 10 In addition, the fixed combination showed beneficial effects regarding the cardiovascular risk profile in a nonselected patient population with insufficient glycemic control, under daily routine conditions in a recent survey. 11 The purpose of this trial was to investigate the effects of a fixed combination of pioglitazone with metformin given twice daily in comparison with a combination of metformin with glimepiride on lipid metabolism, insulin resistance, b-cell dysfunction, chronic systemic inflammation, and the activity of the visceral adipose tissue in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…In women with PCOS, pioglitazone treatment was found to improve the irregularities of menses and hirsutism, reduce insulin resistance, increase the ovulation rate and improve hyperandrogenemia (25)(26)(27)(28). Pioglitazone and metformin fixed-dose combination therapy was demonstrated to be well tolerated, with reduced or similar adverse event rates in treating patients with T2DM compared with each individual monotherapy (29). In addition, it was found that combined treatment with letrozole, metformin and pioglitazone was efficacious among women with PCOS resistant to clomifene citrate, and it was similar to that of combined treatment with clomifene citrate, metformin and pioglitazone (14).…”
Section: Introductionmentioning
confidence: 99%